2013
DOI: 10.1007/s00127-013-0708-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of internet-delivered mental health treatments for rural populations

Abstract: There is considerable potential for internet-delivered treatments to increase service accessibility to some sub-groups, particularly among people with mental health problems who are not currently seeking help. Resistance to internet treatments appears to be largely attitudinal, suggesting that enhancing community education and familiarity with such programs may be effective in improving perceptions and ultimately access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Preparedness to use the internet was higher among those reporting MH problems and other service contacts, which is consistent with earlier findings [26,43]. However, while internet-delivered treatments may eventually improve rural residents’ access to MH resources [20], at present they are subject to many of the same barriers as traditional MH services.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Preparedness to use the internet was higher among those reporting MH problems and other service contacts, which is consistent with earlier findings [26,43]. However, while internet-delivered treatments may eventually improve rural residents’ access to MH resources [20], at present they are subject to many of the same barriers as traditional MH services.…”
Section: Discussionsupporting
confidence: 87%
“…8.1%), which may largely reflect the older age of the ARMHS sample. Selected data from the ARMHS 3-year follow-up have also been examined [26] to try to better understand the feasibility of using internet-delivered MH treatments among rural populations, together with relevant barriers (e.g., internet availability, treatment acceptability, previous exposure).…”
Section: Introductionmentioning
confidence: 99%
“…There is also access to isolation; hence it is easier not to be found in rural areas until it is too late, following potentially less lethal means such as hanging or overdose. There are also issues around help-seeking behaviours and rural culture [58, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, recent research has indicated the efficacy of a clinicianassisted computerised treatment program for depression and alcohol/ other drug use problems, with equivalent benefits reported for both depression and alcohol use as an entirely therapist-delivered treatment [42,44]. The Internet (and related technologies) show promise as a means of closing the gap between evidence and clinical practice in this context [42,45,46].…”
Section: Discussionmentioning
confidence: 99%